The Use of Computational Fluid Dynamics and Discrete Element Modeling to Understand the Effect of Cell Size and Inflow Rate on Flotation Bank Retention Time Distribution and Mechanism Performance - Jens Lichter; Alexander V. Potapov; Richard Peaker (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
"The recent combination of Computational Fluid Dynamics (CFD) and Discrete Element Modeling (DEM) can provide considerable insight into the performance of flotation cells. One area of interest from a fundamental equipment design perspective has been the influence of flotation cell size and the inflow rate on the metallurgical performance of the cell. One of the specific design objectives when increasing the size of flotation cells, or increasing the feed flow to the flotation cell, is to ensure that the feed stream flowing into the cell does not have an opportunity to bypass the mechanism.This paper describes the initial modeling efforts to quantify the inter-relationship of cell size, inflow rates, and feed and discharge box placement, on the retention time distribution of solids in the flotation cell, and the fraction of particles that bypass the mechanism on a size by size basis.INTRODUCTIONThe great majority of newly installed cells in mineral processing plants world-wide are of the cylindrical tank design and this tank shape offers a number of hydraulic advantages over the older style of square cells. Cylindrical cells give symmetrical flow patterns and by careful design of the mechanism and tank internals, the flow patterns generated can concentrate the more intense mixing in the lower portion of the cell to promote good solids suspension and particlebubble contact. Simultaneously, cylindrical tank design gives a more quiescent upper zone for particle-bubble transport into the froth zone. These symmetrical flow patterns are naturally disturbed in normal operation by the slurry inflow and outflow from the individual cells. The challenge for flotation cell designers is to determine the magnitude of these flow disturbances, and to assess whether or when the inflow and outflow rates have a sufficient impact on the hydraulic flow patterns so as to potentially affect the metallurgical performance of the flotation cell."